Transatlantic Puritanism and American Singularities. Issue 1 (3rd January 2017) - HALL, DAVID D.
Abstract : The taunting question posed in the 1820s by the English critic Sidney Smith, 'Who reads an American book?', has long since tumbled into the dustbin of literary history. Yet it continues to reverberate in how Americanists describe the workings of Puritanism in their own country, its presence felt in two respects. One of these is resentment at the indifference to their own work of historians of the Puritan movement in Britain. Another is the assumption among Americanists that the Puritanism of the colonists who arrived in the early seventeenth century was singular in certain respects, be it their sense of 'errand', their modifications of Reformed orthodoxy, or perhaps their daring experiment with a congregation-centred polity, the 'New England Way'. Whenever historians turn to the larger project of Church and State in colonial and modern America, assertions of singularity dominate the telling of our religious history. Do these endeavours warrant returning to Sidney Smith's question and rephrasing it to ask whether Americanists are making the most of European studies of Reformed theology, Puritanism in Britain, and conformity or dissent?